2021
DOI: 10.3390/ijms22147453
|View full text |Cite
|
Sign up to set email alerts
|

Antimelanogenesis Effects of Theasinensin A

Abstract: Theasinensin A (TSA) is a major group of catechin dimers mainly found in oolong tea and black tea. This compound is also manufactured with epigallocatechin gallate (EGCG) as a substrate and is refined after the enzyme reaction. In previous studies, TSA has been reported to be effective against inflammation. However, the effect of these substances on skin melanin formation remains unknown. In this study, we unraveled the role of TSA in melanogenesis using mouse melanoma B16F10 cells and normal human epidermal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…B16F10 cells were treated with α-MSH (100 nM) for 48 h within or without Lm-ME or arbutin. To analyze melanin secretion, the medium was incubated for 48 h and detected at 475 nm [ 52 ]. To evaluate the melanin content, the cells were harvested in e-tubes and washed with cold PBS twice.…”
Section: Methodsmentioning
confidence: 99%
“…B16F10 cells were treated with α-MSH (100 nM) for 48 h within or without Lm-ME or arbutin. To analyze melanin secretion, the medium was incubated for 48 h and detected at 475 nm [ 52 ]. To evaluate the melanin content, the cells were harvested in e-tubes and washed with cold PBS twice.…”
Section: Methodsmentioning
confidence: 99%
“…In human epidermal melanocytes (NHEM cells), Lim et al determined the cytotoxic effects at concentrations above 50 μM after 48 h of theasinensin A incubation. In contrast, no change in cell viability was observed in B16F10 skin melanoma cells in a concentration range up to 25 μM . The results suggest that different cell types and organs have to be considered for cytotoxicity evaluation.…”
Section: Results and Discussionmentioning
confidence: 70%
“…In contrast, no change in cell viability was observed in B16F10 skin melanoma cells in a concentration range up to 25 μM. 37 The results suggest that different cell types and organs have to be considered for cytotoxicity evaluation. Moreover, HepG2 cells were chosen in this study to reproduce the human pathways with the liver as a metabolizer of ingested tea catechins and oxidation products.…”
Section: Cytotoxicity Determination Via Resazurin Assaymentioning
confidence: 75%
“…A previous study indicated that humans and mice share a number of common genetic features and mice and murine cultured cells are typically used instead of human equivalents in biological experiments ( 31 ). A number of reagents have been found to have similar effects on mouse melanoma B16 cells and human epidermal melanocytes ( 32 35 ). It was hypothesized that the effects of PLP on melanogenesis in mouse melanoma cells and human melanocytes are likely to be similar, but further research is necessary as animal models provide only an approximation of the situation in humans.…”
Section: Discussionmentioning
confidence: 99%